Deep eutectic solvent-based headspace single-drop microextraction of polycyclic aromatic hydrocarbons in aqueous samples - Mehravar, Amir; Feizbakhsh, Alireza; Sarafi, Amir Hosein Mohsen; Konoz, Elaheh; Faraji, Hakim (Journal of Chromatography A, 2020)
•Overcoming the challenges of conventional headspace SDME.•Sustainable, Inexpensive, and nontoxic DES was applied as an extracting phase.•An easy, sensitive, and effective method for monitoring PAHs in aqueous samples.•Sample clean-up and analytes pre-concentration simultaneously in a single step. An improved deep eutectic solvent (DES)-based headspace single-drop microextraction procedure has been developed as a green procedure for gas chromatography-mass spectrometric analysis of polycyclic aromatic hydrocarbons (PAHs) in aqueous samples. The stability of the micro-drop was significantly improved using a DES as an extraction phase and a bell-shaped tube as a supporter. These strategies helped to perform the extraction process in higher temperatures and stirring rates. Finally, the back-extraction of the analytes into a proper solvent that is compatible with the chromatography system was applied. The efficacy of the independent variables on the extraction efficiency was evaluated via chemometric methods in two steps. The best result was obtained with choline chloride-oxalic acid at the molar ratio of 1:2, a stirring speed of 2000 rpm for 10 min as well as a sample temperature of 50 °C and with ionic strength prepared by using a 10% (w/v) NaCl. The method indicated a good linearity for the analytes (R2≥0.9989). Under optimal conditions, the analytical signal was linear in the range of 0.01–50 μg L−1. Limit of detection (LOD) and limit of quantification (LOQ) were evaluated at the concentration levels of 0.003–0.012 and 0.009–0.049 μg L−1, respectively. Intraday and interday precision for all targeted compounds was less than 7.2% and 11.3%, respectively. Consequently, the proposed procedure was efficiently applied to extract and analyze the 16 target compounds in real aqueous samples representing satisfactory recoveries (94.40–105.98%).